Racial discrimination and household chores - Shoshana Grossbard; José Ignacio Giménez; José Alberto Molina (Institute for the Study of Labor (IZA), 2010)
We make the novel argument that time spent on household chores can possibly reflect racial discrimination based on color. Our model, based on Becker's theory of allocation of time and his theory of marriage, recognizes that both intra-household bargaining and hedonic marriage markets operating with the help of an implicit price mechanism can lead to a premium for those who perform chores work in households and have lighter skin than their partners. Conversely, those with darker skin need to pay a compensating differential. To test our model, we design a 'race difference' scale that captures each partner's race and ranges between 2 and -2. Based on the American Time Use Survey 2003-2009 we find that for every unit bringing a couple closer to the case of a White respondent and a Black partner, the respondent reduces his or her weekly hours of chores work by 37 minutes. Marriage markets appear to be influenced by racial discrimination based on color.
Keywords: D13; I21; J12; J22; 330; time use; racial discrimination; household chores; compensating differentials